Economic Value of the Services Provided by Florida Springs and Other Water Bodies: A Summary of Existing Studies - Sara Wynn; Tatiana Borisova; Alan Hodges (EDIS, 2014)
Florida residents and visitors place a high value on aquatic natural resources. This 8-page fact sheet reviews nine studies that demonstrate that Florida’s springs have a very large economic value, both for recreation and resource conservation. In these studies, economists measure the value of ecosystem services in dollar terms to assist management decisions concerning natural resources. Willingness to pay studies show that people who benefit from Florida springs place a high value on them. Economic contribution studies show that Florida springs play a significant role in local and state economic health and job creation. Written by Sara Wynn, Tatiana Borisova, and Alan Hodges, and published by the UF Department of Food and Resource Economics, November 2014. (UF/IFAS Photo by Tyler Jones.)